2018
DOI: 10.1017/s0956792518000128
|View full text |Cite
|
Sign up to set email alerts
|

The infinitesimal phase response curves of oscillators in piecewise smooth dynamical systems

Abstract: The asymptotic phase θ of an initial point x in the stable manifold of a limit cycle (LC) identifies the phase of the point on the LC to which the flow φt(x) converges as t → ∞. The infinitesimal phase response curve (iPRC) quantifies the change in timing due to a small perturbation of a LC trajectory. For a stable LC in a smooth dynamical system, the iPRC is the gradient ∇x(θ) of the phase function, which can be obtained via the adjoint of the variational equation. For systems with discontinuous dynamics, the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 56 publications
3
34
0
Order By: Relevance
“…In Refs. [47,48], phase equations for hybrid limit-cycle oscillators have been derived. A generalized adjoint equation with discontinuous jumps is derived and the sensitivity function for the phase is obtained.…”
Section: Generalization Of Phase Reduction To Non-conventional Sysmentioning
confidence: 99%
“…In Refs. [47,48], phase equations for hybrid limit-cycle oscillators have been derived. A generalized adjoint equation with discontinuous jumps is derived and the sensitivity function for the phase is obtained.…”
Section: Generalization Of Phase Reduction To Non-conventional Sysmentioning
confidence: 99%
“…This model exhibits a stable limit-cycle oscillation for appropriate parameter values that corresponds to periodic movements of the legs. This is a four dimensional hybrid dynamical system with impacts, hence it cannot be dealt with by the conventional methods [10,33,34] mentioned above.…”
Section: B Passive Bipedal Walkermentioning
confidence: 99%
“…Existence and mechanisms of chaos as a result of a discontinuous voltage reset has been shown in a Fitzhugh-Nagumo model by calculating the Lyapunov exponents: a result enabled by the saltation matrix [28]. Assuming continuous solutions in a discontinuous vector field Park et al (2018) derived the size of discontinuities in the iPRC from first principles [29] and showed that the calculation is closely related to the saltation matrix [3]. For hybrid systems with discontinuous solutions, Coombes et al (2012) derived the iPRC for a piecewise linear IF model [8] by normalizing on each segment away from discontinuities.…”
Section: Adjoint Methods (Nonsmooth Systems)mentioning
confidence: 99%